Perbedaan Status Gizi, Tingkat Konsumsi Gizi, Aktivitas Fisik dan Kebugaran Jasmani (Studi pada Siswa yang Mengikuti Ekstrakurikuler Pencak Silat dan Futsal di Sekolah Menengah Kejuruan Teuku Umar Kota Semarang Tahun 2017) - Ulfa, Nastiti Almira; Widajanti, Laksmi; Suyatno, Suyatno (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Nutritional status is the state of the body as a result of food consumption and the use of nutrients. Physical fitness is the body's ability to perform daily tasks and tasks diligently, without experiencing significant fatigue. The degree of individual health and fitness is affected by age, sex, genetics, nutritional status, and physical activity. Physical activity / physical exercise is good, true, measurable, and regular can improve the degree of health and physical fitness. The purpose of this research was to analyze the differences of nutritional status, the level of nutritional consumption, physical activity and physical fitness in students who follow extracurricular between pencak silat and futsal. This research uses quantitative research method with cross sectional research design. Population of this research were 22 students who follow extracurricular pencak silat and futsal. Sample size of this research were 17 students who fulfilled inclusion and exclusion criteria. Sampling technique in this research use purposive sampling. Data analysis using Independent Samples T test and Mann Whitney test. The results showed that the average nutritional status of students extracurricular pencak silat 3.20 and futsal 3.14. The average of energy consumption level of extracurricular students of pencakl silat 1.90 and futsal 2.00. The average of protein consumption level of extracurricular students of pencak silat 1.80 and futsal 2.00. Median of physical activity of students extracurricular of pencak silat 3.00 and futsal 2.00. Median of physical fitness of students extracurricular pencak silat 3.00 and futsal 3.00. The result of statistical test showed that there was no difference in nutritional status (p = 0,165), energy consumption level (p = 0,971) and protein (p = 0,746) and physical fitness (p = 0,071) but there was difference in physical activity (p = 0,032 ) Students who follow extracurricular between pencak silat and futsal. This study recommends for students who follow extracurricular pencak silat and futsal to increase nutritional intake and physical activity so that the nutritional status and physical fitness of students can be optimal and maintained